DATA MINING SISTEM TATA LETAK MATERIAL DI PT BATAM CYCLECT - Hutapea, Yuni Shantika; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2021)
PT BATAM CYCLECT or better known as Cyclect is a company engaged in the electrical sector in the shipyard. PT BATAM CYCLECT in its material warehouse lacks good material arrangement procedures in the warehouse which results in the warehouse looking cramped and less orderly. So a system is created that helps in processing material layout data based on the type of item, such as material consumables, electric materials, welding materials, electric tools, chemical materials and many other types. Data Mining is a solution in developing a business or a way to use data for future prediction processes. The method used is association rules to find associative rules that are connected with one item and another. The Apriori Algorithm is an algorithm used to generate association rules and is well-known in determining high frequency patterns. The goal is to make it easier for the storeman in the waiter and shorten the time when searching for goods simultaneously with the material layout system. The Apriopri algorithm takes advantage of this process to reduce or narrow the search space for itemset candidate frequency. To test the accuracy of the Apriori algorithm using the Rapid Miner software. The results of the research carried out obtained 10 association rules with a minimum support value of 5% and 50% confidence with 3-itemset results, namely if you order Marking Tape and markers you will order PVC Insulation Tape with a Support value of 15% and a confidence value of 89%.